WOMEN EMPOWERMENT AND LEADERSHIP: YOUTH AS AGENTS OF SOCIAL CHANGE - Abdurakhmonova Iroda Xolbozor qizi (Western European Studies, 2025)
This article examines the central position of young women as social change makers, comparing women's empowerment in Uzbekistan to that in India. The article argues that empowerment of women is central to national development. The progress of Uzbekistan includes higher political engagement of women, social programs for women, more education, and more job opportunities. Initiatives in India, i.e., "Beti Bachao, Beti Padhao," are also mentioned. The article addresses challenges in unconventional areas, emphasizing the importance of education. The empowerment of young women is encouraged, recognizing their potential to be social change makers and to facilitate Uzbekistan-India cooperation. The IndiaCentral Asia Youth Forum is a central platform for this
Keywords: opportunity; education; gender equality